Labor Market Concentration in Germany - Michael Oberfichtner; Martin Popp (Institute of Labor Economics (IZA), 2025)
Using register data, we document that the average German labor market, defined by hires in combinations of 3-digit occupations, requirement levels, and commuting zones, is highly concentrated (HHI=0.257). By EU antitrust thresholds, 56 percent of these labor markets feature moderate or high concentration, covering 9 percent of workers. Concentration remained relatively stable between 2012 and 2023. The labor market delineation strongly affects the measured level of concentration but not its evolution, whereas the choice of the firm size variable has little influence. Concentration differs starkly across occupations and regions, and workers in complex jobs experience the highest levels of concentration.
Keywords: J42; L10; J60; 330; monopsony power; labor market concentration; occupations